CANDLE Syndrome: A Recently Described Autoinflammatory Syndrome. Issue 4 (May 2015) - Tüfekçi, Özlem; Bengoa, ŞebnemYilmaz; Karapinar, Tuba Hilkay; Ataseven, Eda Büke; İrken, Gülersu; Ören, Hale
Abstract : CANDLE syndrome (chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature) is a recently described autoinflammatory syndrome characterized by early onset, recurrent fever, skin lesions, and multisystemic inflammatory manifestations. Most of the patients have been shown to have mutation in PSMB8 gene. Herein, we report a 2-year-old patient with young onset recurrent fever, atypical facies, widespread skin lesions, generalized lymphadenopathy, hepatosplenomegaly, joint contractures, hypertrglyceridemia, lipodystrophy, and autoimmune hemolytic anemia. Clinical features together with the skin biopsy findings were consistent with the CANDLE syndrome. The pathogenesis and treatment of this syndrome have not been fully understood. Increased awareness of this recently described syndrome may lead to recognition of new cases and better understanding of its pathogenesis which in turn may help for development of an effective treatment.